IMPLEMENTASI PROGRAM PENGEMBANGAN DESTINASI PARIWISATA DI WIDURI WATER PARK KABUPATEN PEMALANG - Titi Nur Maulida; Aloysius Rengga; Ari Subowo (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
The development of tourism is one of the strategies to introduce a specific area as a tourist area and to increase local revenue. This study aims to determine how the Tourism Development Program Implementation in the Widuri Water Park Pemalang. This study is a qualitative study using descriptive analysis as data techniques. In this study, the concept of the theory is a theory used belongs to Meerile S. Grindle that the variable success implementation is contents of policy and context of policy. The development of tourism destinations affects on development around the area attractions. the purpose of enhancing the competitiveness of the tourism program in Pemalang district can be reached. Tourist visits decrease proved by the data indicating approximately 1.8% of visitors decreased each year because there are many things such as tourism maintenance that is not good enough and less of visitors’ interest from outer of Pemalang district. The tourism destination development program implemented by Department of Culture and Tourism only related to development and maintenance of facilities and infrastructure. However, if it is seen from the strategic plan, many other activities that can be done to achieve the goal. Activities in this program cannot be implemented due to various factors such as the lack of coordination and understanding of the program objectives. The conclusion of this study describes that the implementation of Tourism Destination Development Program in the Widuri Water Park has not been implemented effectively and maximum because there are still constraints in planning and budgeting. Suggestion that the writer can convey is that the implementation of tourism destination development program carried out in accordance with the strategic plan that was made despite the constraints affecting.